Examining health care providers’ and middle-level managers’ readiness for change: a qualitative study - Austin, Tujuanna; Chreim, Samia; Grudniewicz, Agnes (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Readiness is a critical precursor of successful change; it denotes whether those involved in the change are motivated and empowered to participate in the change. Research on readiness tends to focus on frontline providers or individuals in non-managerial positions and offers limited attention to individuals in middle management positions who are expected to lead frontline providers in change implementation. Yet middle-level managers are also recipients of changes that are planned and decreed by those in higher positions. This study sought to examine both frontline provider and middle manager readiness for change in the context of primary care program integration. Methods Using a qualitative case study approach, we examined how frontline providers and middle managers experienced six readiness factors: discrepancy, appropriateness, valence, efficacy, fairness and trust in management. Data were collected through documents, meeting observation and semi-structured interviews with frontline providers and middle managers involved in the change. Results The findings highlighted similarities and differences in readiness experiences of frontline providers and middle managers. Across both types of participants, we found that the notion of valence should be expanded to consider individuals’ evaluation of benefits to patients and the health system; efficacy applies to both content and process of change; fairness and trust in management findings require further exploration to determine their appropriateness to be incorporated in models of readiness for change; and trust in management (or lack of trust) has a cascading influence across the levels in the organization. Conclusions Our study makes a contribution by nuancing and extending conceptualizations of individual readiness factors, and by highlighting the central role of middle manager readiness for change. Implications of the study include the need to consider readiness factors prior to the implementation of change and the importance of fostering readiness throughout all levels of the organization.